1999
DOI: 10.1080/080394899426873
|View full text |Cite
|
Sign up to set email alerts
|

Heroin dependence: Consequences and precursors related to route of administration

Abstract: R. Heroin dependence: Consequences and precursors related to route of administration. Nord J Psychiatry 1999;53:153-158. Oslo. ISSN 0803-9488. Two random samples of Danish prisoners on remand (solitary confinement (SC) and non-SC)) were examined using semistructured and standardized psychiatric and social interviews, cognitive tests, and questionnaires. Heroin dependence was divided into injection heroin dependence (IHD) and smoke heroin dependence (SHD). Comparisons corrected for confounders were made wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
9
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(9 citation statements)
references
References 11 publications
(20 reference statements)
0
9
0
Order By: Relevance
“…Furthermore, risk behaviors related to non-injection forms of substance use (e.g., the sharing of cocaine or crack use paraphernalia) have been tentatively associated with possible HCV transmission [33][34][35] . As for mental health, Andersen et al [23] found a higher prevalence of psychiatric disorders in the injector group compared to non-injectors in a prisoner sample. Dinwiddie et al [30] reported higher rates of antisocial personality disorder -but no differences for mood disorders -for injectors in comparison to non-injectors in a sample of street drug users.…”
Section: Introductionmentioning
confidence: 99%
See 4 more Smart Citations
“…Furthermore, risk behaviors related to non-injection forms of substance use (e.g., the sharing of cocaine or crack use paraphernalia) have been tentatively associated with possible HCV transmission [33][34][35] . As for mental health, Andersen et al [23] found a higher prevalence of psychiatric disorders in the injector group compared to non-injectors in a prisoner sample. Dinwiddie et al [30] reported higher rates of antisocial personality disorder -but no differences for mood disorders -for injectors in comparison to non-injectors in a sample of street drug users.…”
Section: Introductionmentioning
confidence: 99%
“…Heroin injectors tend to start drug use at an earlier age than non-injectors [12,23] , who typically indicate shorter duration of regular drug use [12,[14][15][16]24] . Injectors often indicate more intense patterns of drug use, as expressed through higher levels of dependence or higher frequency of use [14,[24][25][26][27] , and consequently higher drug expenditures [28] .…”
Section: Introductionmentioning
confidence: 99%
See 3 more Smart Citations